Principles for task shifting hypertension and diabetes screening and referral: a qualitative study exploring patient, community health worker and healthcare professional perceptions in rural Uganda - Rebecca Ingenhoff; Richard Munana; Ivan Weswa; Julia Gaal; Isaac Sekitoleko; Hillary Mutabazi; Benjamin E. Bodnar; Tracy L. Rabin; Trishul Siddharthan; Robert Kalyesubula; Felix Knauf; Christine K. Nalwadda (BMC, 2023)
Abstract Background A shortage of healthcare workers in low- and middle-income countries (LMICs) combined with a rising burden of non-communicable diseases (NCDs) like hypertension and diabetes mellitus has resulted in increasing gaps in care delivery for NCDs. As community health workers (CHWs) often play an established role in LMIC healthcare systems, these programs could be leveraged to strengthen healthcare access. The objective of this study was to explore perceptions of task shifting screening and referral for hypertension and diabetes to CHWs in rural Uganda. Methods This qualitative, exploratory study was conducted in August 2021 among patients, CHWs and healthcare professionals. Through 24 in-depth interviews and ten focus group discussions, we investigated perceptions of task shifting to CHWs in the screening and referral of NCDs in Nakaseke, rural Uganda. This study employed a holistic approach targeting stakeholders involved in the implementation of task shifting programs. All interviews were audio-recorded, transcribed verbatim, and analyzed thematically guided by the framework method. Results Analysis identified elements likely to be required for successful program implementation in this context. Fundamental drivers of CHW programs included structured supervision, patients' access to care through CHWs, community involvement, remuneration and facilitation, as well as building CHW knowledge and skills through training. Additional enablers comprised specific CHW characteristics such as confidence, commitment and motivation, as well as social relations and empathy. Lastly, socioemotional aspects such as trust, virtuous behavior, recognition in the community, and the presence of mutual respect were reported to be critical to the success of task shifting programs. Conclusion CHWs are perceived as a useful resource when task shifting NCD screening and referral for hypertension and diabetes from facility-based healthcare workers. Before implementation of a task shifting program, it is essential to consider the multiple layers of needs portrayed in this study. This ensures a successful program that overcomes community concerns and may serve as guidance to implement task shifting in similar settings.